A Compatible Estimation Model of Stem Volume and Taper for Acacia mangium Willd. Plantations - Krisnawati, Haruni (Indonesian Journal of Forestry Research, 2016)
A compatible volume estimation model for Acacia mangium Willd. was developed from data corresponding to 279 felled sample trees collected from the A. Mangium plantations in South Sumatra, Indonesia. The model comprises a total volume model and a stem taper model, which is compatible in the sense of the total volume obtained by integration of the taper model being equal to that computed by the total volume model. Several well-known total volume functions were evaluated. A logarithmic model was determined to be best and was then used as the basis for deriving the taper model. Appropriate statistical procedures were used in model fitting to account for the problems of heteroscedasticity and autocorrelation that are associated with the construction of volume and taper functions. The developed model can be used to estimate total stem volume, merchantable volume to any merchantability limit, diameter of any height, and (possibly) height of any diameter based on only easily measurable parameters such as diameter at breast height and total tree height for the species analysed. The models provide a major improvement over the previous models for A. mangium plantations in Indonesia which were only applicable for estimating stem volume to a fixed top diameter limit.